Effect of icariin on ovarian cancer: a combined network pharmacology and meta-analysis of in vitro studies approach - Cao, Shang-Mei; Chen, Bo-Lin; Zou, Zhen-Zhen; Yang, Shao-Zhe; Fu, Xiu-Hong (Frontiers in Pharmacology, 2024)
An abundance of experimental evidence indicates that icariin (ICA) could potentially exert an anti-tumor effect on ovarian cancer (OC). Nevertheless, the reliability of this evidence remains ambiguous. This study aimed to explore the impact of ICA on OC and the underlying mechanisms. Bioinformatics analysis was employed to pinpoint ICA-targeted genes and signaling pathways implicated in OC, utilizing network pharmacology. Subsequently, PubMed, EMBASE, and Web of Science databases were systematically searched from 2001 through June 2023 for in vitro trials evaluating the anti-tumor efficacy of conventional ICA versus placebo in OC. The pathways and genes identified in the literature were recorded, and the therapeutic targets were statistically analyzed and compared with the predicted targets from network pharmacology to confirm the precision of the targets. Fourteen target genes were validated with success. The pathways corresponding to the remaining genes-excluding these 14-were analyzed and found to be primarily associated with cell apoptosis, anti-tumor, and other related pathways. Out of the 76 studies retrieved, eight fulfilled the inclusion criteria. The subsequent meta-analysis suggested that ICA treatment was significantly correlated with reduced cell growth and induced apoptosis. This study demonstrated a certain efficacy of ICA compared to placebo in enhancing anti-tumor outcomes, characterized by increased abilities in reducing cell growth and inducing apoptosis. The pathways involved in the therapeutic effect may be linked to cell apoptosis and anti-tumor mechanisms.